2007
DOI: 10.1016/j.rmed.2007.02.025
|View full text |Cite
|
Sign up to set email alerts
|

The association of OSA with insulin resistance, inflammation and metabolic syndrome

Abstract: Obstructive sleep apnea (OSA) shares many cardiovascular risk factors with metabolic syndrome, including obesity, hypertension, insulin resistance, and pro-inflammatory state. This study aimed to examine the possible association of OSA severity with insulin resistance, inflammation and the metabolic syndrome. Ninety eight patients suspected for OSA (54.9+/-13.1 years) were studied. Overnight polysomnography and blood sampling was taken for glucose, insulin, high-density lipoprotein(HDL)-cholesterol, triglyceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 37 publications
5
72
1
5
Order By: Relevance
“…Similar data have been obtained in samples of OSA patients (tables 3 and 4) [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80], with a large prevalence of positive [63,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] rather than negative [78][79][80] studies. In clinical populations, OSA patients characterised by full-PSG were significantly more likely to have impaired glucose tolerance (IGT) and diabetes than subjects free of OSA syndrome (OSAS) [71].…”
Section: Physiological and Clinical Datasupporting
confidence: 74%
“…Similar data have been obtained in samples of OSA patients (tables 3 and 4) [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80], with a large prevalence of positive [63,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] rather than negative [78][79][80] studies. In clinical populations, OSA patients characterised by full-PSG were significantly more likely to have impaired glucose tolerance (IGT) and diabetes than subjects free of OSA syndrome (OSAS) [71].…”
Section: Physiological and Clinical Datasupporting
confidence: 74%
“…3). MetS is diagnosed in clinical practice by the NCEP-ATP (National Cholesterol Education ProgrammeAdult Treatment Panel) III criteria, which require the presence of three out of five criteria [36][37][38][39][40][41][42][43][44][45]. The number of MetS criteria is defined as the metabolic index and can be used as an indicator of severity of metabolic abnormalities.…”
Section: Osa Visceral Fat and The Metabolic Syndromementioning
confidence: 99%
“…2,3 OSAS has been shown to increase the risk of hypertension, stroke, and cardiovascular disease. [4][5][6] In addition, clinical studies have reported that OSAS increases morbidity from crashes caused by daytime somnolence, and have focused on the diagnosis, treatment, and prevention of OSAS. 2 Obesity, male sex, older age, alcohol use, genetic factors, and a narrowed upper airway are well-known risk factors for OSAS, and smoking may be a risk factor for sleep apnea or snoring.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%